Peningkatan Kemampuan Mengenal warna melalui Kegiatan Finger Painting Pada Anak Kelomok B Di TK Rahayu Samarinda - Meliawati, Dita; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
The research was conducted at Rahayu Samarinda Kindergarten in the 2019-2020 academic year. The background of this research was the lack of development in recognizing colors in children in finger painting activities. Formulation of the problem to be studied Based on the background of the problem that has been stated above, through this research it can be formulated how to increase the ability to recognize colors through finger painting activities in group B1 children at TK Rahayu Samarinda. colors with finger painting activities in group B at TK Rahayu Samarinda. This type of research is used in classroom action research (CAR). Research is a scientific series in the context of solving a problem. Research results are never included as a direct solution to the problems to be faced. Based on the results of the research and discussion that was carried out in the third cycle of 3 meetings in each cycle, it can be concluded that the finger painting activity in group B1 at TK Rahayu Samarinda was able to improve the ability to recognize colors through finger painting activities